Group-specific redistribution, inequality, and subjective well-being in China - Peihua Deng; Ronnie Schöb (Review of Income and Wealth, 2023)
Using survey data from the China Family Panel Studies (CFPS) from 2010 to 2018, this paper analyzes the relationship between income inequality, group-specific income redistribution, and subjective well-being among China's urban, rural, and migrant populations. Income redistribution significantly reduces the within-group inequality for urban residents while widening the income gap among urban residents, rural residents, and migrants. Using narrowly defined reference groups, our findings indicate that there is no significant correlation of within-group inequality and subjective well-being of the respective group members. By contrast, the increased income gap between urban and rural residents is positively correlated with the rural residents' subjective well-being. More importantly, the group-specific redistribution inherent in the Hukou system that widens the income gap between urban residents and both migrants and rural residents makes both the aforementioned worse off. The existing Hukou system thus bars the way to implement the concept of " common prosperity " of the Chinese government that aims to foster a more balanced and sustainable development.
Keywords: 330; income inequality; income redistribution; subjective well-being